Trade policy simulation and welfare analysis using a partial equilibrium model: the case of bovine meat in Morocco - Alaoui, Oussama (Kansas State University, 2008)
The impact of agricultural trade liberalization on welfare is a major concern to the Government of Morocco. Several agricultural sectors and sub-sectors that are suffering from severe inefficiencies have been protected by the Government mainly through prohibitive import tariffs as a mean to support the income of domestic producers. Although the rhetoric in Morocco is of trade liberalization, the farm sector, with few exceptions, has largely escaped the general tendency. The livestock sector in general and the bovine meat production in particular figure among the most protected goods in the country. Bovine meat imports are imposed a prohibitive tariff rate of 254 percent. In addition, several technical barriers to trade exist in the form of rigid sanitary regulations. It is strategically important for Morocco's trade partners and those that are planning to negotiate different forms of trade agreements to understand the economic argument behind Moroccan protectionist policy in agriculture. The bovine meat market in Morocco is of high interest to major exporters given the growing size in domestic and tourist populations, the high domestic prices, as well as the increase in consumer awareness. Given its good sanitary status, Australia is a strong candidate for negotiating an agreement that will include bovine meat within a general agricultural package. The objective of this study is to evaluate economic evidence and determine whether or not opening up trade of bovine meat will have a net positive impact on welfare. Such evidence can become a strong argument in the hands of trade negotiators for major exporting nations such as Australia. This study uses data from the United Nations Food and Agricultural Organization (FAO), the Ministry of Agriculture of Morocco and Meat and Livestock Australia (MLA) to construct a partial equilibrium model for the bovine meat market. The model simulates different trade policies: closed market, free trade, quota and TRQ. Using the theory of comparative advantage and the concepts of consumer and producer surpluses, gains and losses are assessed and the net impact on welfare is evaluated. The empirical analysis suggests that total free trade in the bovine meat market results in the highest gain in social welfare when compared to protectionism (USD 246.62 million), followed by the TRQ (USD 206.11 million) and quota policy (USD 4.92 million). As hypothesized, the protectionist policy results in large losses in consumers' surplus. The results of the analysis converge with the economic theory and are compelling evidence for the benefits brought by openness in the bovine meat trade.
Keywords: Beef Trade; Tariff Rate Quota; Meat Imports; Beef Quota; Economics, Agricultural (0503)